2021
DOI: 10.1186/s13054-021-03755-7
|View full text |Cite
|
Sign up to set email alerts
|

Identification of persistent and resolving subphenotypes of acute hypoxemic respiratory failure in two independent cohorts

Abstract: Background Acute hypoxemic respiratory failure (HRF) is associated with high morbidity and mortality, but its heterogeneity challenges the identification of effective therapies. Defining subphenotypes with distinct prognoses or biologic features can improve therapeutic trials, but prior work has focused on ARDS, which excludes many acute HRF patients. We aimed to characterize persistent and resolving subphenotypes in the broader HRF population. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 62 publications
(83 reference statements)
1
16
0
Order By: Relevance
“…On the other hand, our findings regarding persistent severe ARDS seem anticipated. The prevalence of persistent severe ARDS seems similar to non-COVID ARDS [ 11 ] (or even non-COVID acute hypoxemic respiratory failure) [ 25 ] and so is the mortality. This is also in line with findings of a recent observational study from the United Kingdom, which reported that refractory hypoxemia remains a major determinant of mortality in the COVID-19 era [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, our findings regarding persistent severe ARDS seem anticipated. The prevalence of persistent severe ARDS seems similar to non-COVID ARDS [ 11 ] (or even non-COVID acute hypoxemic respiratory failure) [ 25 ] and so is the mortality. This is also in line with findings of a recent observational study from the United Kingdom, which reported that refractory hypoxemia remains a major determinant of mortality in the COVID-19 era [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…15 74 Despite its ubiquitous nature there is no clear definition of AHRF, with most studies and reviews focusing on the ARDS subset of these patients, where the Berlin definition offers a more unambiguous demarcation of the study population. Various AHRF definitions used in the literature can be expressed as a PaO2/FiO2 ratio of <300 mm Hg only, 75 76 a PFR of <200 mm Hg with respiratory support, 73 and a PFR of <300 mm Hg with new pulmonary infiltrates and ventilator support with a PEEP of ≥5 cmH 2 O in the LUNG-SAFE trial. 15 74 The Berlin definition improved on previous classifications by removing the requirement for invasive ventilation, 15 Consequently, there is a significant overlap between currently used AHRF definitions and the Berlin definition, so the question emerges: does ARDS per se confer an additional mortality burden over similarly severe 'other causes' of AHRF?…”
Section: Utility Of Ards/ahrf Distinctionmentioning
confidence: 99%
“…This includes varied clinical presentations such as lobar versus diffuse lung injury, severity of hypoxemia, and most recently the interactions between pro-inflammatory mediators with markers of endothelial dysfunction that distinguish early resolution from persistent hypoxemia. 213 Newer still is examining specific gene expression governing inflammation that might provide a more comprehensive understanding of ARDS, and also the possibility for highly specific novel drug therapies for certain ARDS phenotypes, or perhaps targeting current therapies more effectively. Research in this area already has discerned ARDS sub-phenotypes associated with the spectrum of inflammatory response (ie, uninflamed, reactive, hyporeactive, and hyperreactive), suggesting the existence of treatable traits with implications beyond ARDS.…”
Section: Infant Respiratory Distress Syndrome and Open Lung Ventilationmentioning
confidence: 99%